Sustainability Assessment of Stunting Management through Multidimensional Scaling - Kasyful Fahmi; Nurul Badriyah; Hartati Kartikaningsih (Pusbindiklatren Bappenas, 2025)
Stunting remains a major challenge in Indonesia, requiring assessments that extend beyond prevalence to sustainability. This study evaluates the sustainability of stunting prevention in Batu Rakit Village, North Lombok, using RAPFISH-MDS across five dimensions: economy, ecology, health, social, and governance. Data from 68 households with stunted children were analyzed using validated attributes drawn from policy frameworks and literature. Findings reveal disparities: governance was highly sustainable (81.75%), social (60.28%), and health (56.57%) were moderately sustainable, while ecological (41.16%) and economic (28.86%) remained less sustainable. Key leverage factors included access to social assistance, sanitation, maternal education, exclusive breastfeeding, and cross-sector coordination. The findings underscore that sustainable stunting management depends on synergizing governance and social participation to address economic-ecological vulnerabilities, coupled with the integration of health and social interventions. The Batu Rakit experience offers a relevant model for sustainable stunting reduction in rural Indonesia.